FOLK MEDICINE VAOILAIC RITUALS OF NATIONAL AND RELIGIOUS CHARACTERISTICS - M.A. Karimova; Quchadullayev Rahmatillox Zafarbek son (American Journals Publishing, 2024)
The article provides a philosophical analysis of the national and religious peculiarities of the ancient family rituals and customs of our ancestors. The role of this ceremony and Customs in stabilizing the family environment is shown by the important characteristics of folk medicine.
Keywords: Cauldron, huge house, relative, hand-taking, modern medicine, folk medicine, domains, strong family, National, Religious.